Dilemmatic treatment of recurrent right breast mucinous carcinoma in a 34-year-old pregnant woman: a case report - Widhusadi, Ni Luh Wita Astari; Setiawan, William Alexander (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2023)
Introduction: In females under 35, the incidence of mucinous carcinoma (MC), a rare form of breast carcinoma, is 1%. When pregnancy-associated breast cancer is diagnosed, it presents a challenge to strike a balance between a potentially fatal therapy for the fetus and a life-saving therapy for the mother's breast cancer. This study aimed to present an MC case in a 34-year-old female with seven weeks-old gestations. Case presentation: The 34-year-old woman presented with a lump on her right breast in 2012 and was diagnosed with giant fibroadenoma. Then, an excisional biopsy was performed, and the pathological finding showed a grade II MC. After one year of tumor regression, another mass was found on the same side of the breast. A repeated ultrasound was carried out, and then the patient was scheduled to have a radical mastectomy followed by radiotherapy. During the schedule of radiotherapy, she found out that she was 6-7 weeks pregnant. This condition brought a new problem since there was a chance that the radiotherapy may have affected the fetus. Therefore, the radiotherapy treatment was postponed until the 6-month gestational age or after the delivery of the baby. Conclusion: Our case report shows the complexity of judgments to achieve the holistic treatment of our patient's condition. Furthermore, the determination of 'wait-and-observe' could be contemplated for the characteristics of the tumor and the patient's decision.